1983
DOI: 10.1017/s0033291700047966
|View full text |Cite
|
Sign up to set email alerts
|

The association of affective disorder with Huntington's Disease in a case series and in families

Abstract: SynopsisMajor affective disorder clinically similar to the disorder found in conditions other than Huntington's Disease (HD) was found in 41% of patients with HD in a consecutive case series ascertained through multiple sources in a defined geographical area. The association appears to be confined to certain families, and affective disorder may appear as long as 20 years before the onset of chorea and dementia. The association may represent genetic heterogeneity in HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
5

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(84 citation statements)
references
References 21 publications
2
77
0
5
Order By: Relevance
“…In fact, Folstein et al [46] observed that depression might occur up to 5 years prior to onset of movement abnormalities. Shiwach [2] also found, in a sample of 110 patients with HD, that the lifetime prevalence of depression was almost 40%.…”
Section: Affective Disorders and Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Folstein et al [46] observed that depression might occur up to 5 years prior to onset of movement abnormalities. Shiwach [2] also found, in a sample of 110 patients with HD, that the lifetime prevalence of depression was almost 40%.…”
Section: Affective Disorders and Suicidementioning
confidence: 99%
“…Sertraline [44] Case series, 7 Improvement (marked in five, moderate in two); one patient treated concomitantly with risperidone for psychotic depression; two patients treated with lorazepam for sleep Fluoxetine [42] Open label trial, 8 Improvement in mood and function Fluoxetine and l-deprenyl [93] Case report, 1 with paranoia and aggression Improvement in all three psychiatric symptoms ECT [94] Retrospective case reports, 6 (five unipolar depressed patients; one bipolar depressed patient) Improvement in four of the unipolar patients and in the bipolar patient; patients with prominent delusions showed the most benefit; apathy showed the least improvement Clozapine [95] Case report, 1 with psychotic depression Improvement Sulpiride [96] Case report, 1 Improvement Phenelzine and isocarboxazid [97] Case series, 3 Improvement of mood; two of three patients showed improvement with concomitant psychosis Amoxapine [98] Case report, 1 Improvement ECT [46] Retrospective case reports, 2 Improvement TCA [43] Open trial, 6 Five of six patients improved, but only on neurovegetative symptoms TCA [99] Open trial, 10 Seven had some improvement of depression; sedation and anticholinergeric side effects seen in some, and some patients give neuroleptics Amytriptyline or chlorpromazine [100] Open trial, 4 (three given amytriptyline, one given chlorpromazine)…”
Section: Comments and Outcome On Target Symptomsmentioning
confidence: 99%
“…The spectrum of psychiatric features characteristic of HD includes apathy, irritability, depression and anxiety, pathological impulse control, disinhibition and executive dysfunction (Folstein et al, 1983, Shiwach and Norbury, 1994, Julien et al, 2007, Wolf and Kloppel, 2013. One of only two available brain imaging studies investigating psychiatric progression in HD attributed increased levels of irritability in premanifest HD to reduced coupling between amygdalae and orbitofrontal cortex (Kloppel et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[2,7]. Die psychiatrischen Manifestationen können dem Auftreten eindeutiger neurologischer Symptome dabei bis zu 20 Jahre vorausgehen [9]. Wie unsere Falldarstellungen zeigen, führt die enorme phänotypische Heterogenität einer HD sowie ihr mögliches spontanes Auftreten auch 10 Jahre nach der Charakterisierung der zugrunde liegenden genetischen Mutation im klinischen Alltag noch zu differenzialdiagnostischen Schwierigkeiten [30,10].…”
Section: Diskussionunclassified